The effect of treatment with Campath-1H in patients with autoimmune cytopenias. - Willis, F; Marsh, J; Bevan, D; Killick, S; Lucas, G; Griffiths, R; Ouwehand, W; Hale, G; Waldmann, H; Gordon-Smith, E (2001)
We describe 21 patients with severe and life-threatening autoimmune cytopenias resistant to standard immunosuppression who were treated with the monoclonal antibody Campath-1H. Four patients had autoimmune neutropenia, four had autoimmune haemolytic anaemia, four had pure red cell aplasia, one had immune thrombocytopenia purpura (ITP), three had autoimmune haemolytic anaemia and ITP (Evan's syndrome), three had autoimmune pancytopenia (ITP, autoimmune neutropenia and autoimmune haemolytic anaemia), one had ITP (associated with acquired Glanzmann's disease) and autoimmune neutropenia, and one had ITP and red cell aplasia. Campath-1H was administered at a dose of 10 mg/d as an intravenous infusion for 10 d. Responses were seen in 15 patients, which were sustained in six. Relapse occurred in eight patients after Campath-1H treatment. Patients entering the study later, received cyclosporine after Campath-1H in an attempt to reduce the incidence of relapse. Three patients received a second course of Campath-1H; all responded but later relapsed. Fourteen patients are alive at a median of 12 months (range 4-61) after Campath-1H. Campath-1H represents an alternative therapeutic option for severe, refractory autoimmune cytopenias.